Russia's foreign policy evolution in the new Balkan landscape - Entina, Ekaterina (Array, 2020)
The article reflects on the issue of the foreign policy strategy of modern Russia in the Balkans region. One of the most significant aspects of this problem is the difference in views between Russia and the West. Authors show how different interpretations of the events in former Yugoslavia in the 1990s and the beginning of the 2000s predetermined the sense of mutual suspicion and mistrust which spread to other regions such as the post-Soviet space. Exploring differences between the Russian and the Western (Euro-Atlantic) views on the current matters, authors draw attention to fundamental differences in terminology: while the Western narrative promotes more narrow geographical and political definitions (such as the Western Balkan Six), traditional Russian experts are more inclined to wider or integral definitions such as “the Balkans” and “Central and Southeast Europe”. Meanwhile none of these terms are applicable for analysis of the current trends such as the growing transit role of the Balkans region and its embedding in the European regional security architecture. Therefore, a new definition is needed to overcome the differences in vision and better understand significant recent developments in the region. Conceptualizing major foreign policy events in Central and Southeast Europe during the last three decades (the 1990s, 2000s and 2010s), authors demonstrate the significance of differences in tools and methods between the Soviet Union and the modern Russia. Permanent need for adaptation to changing political and security context led to inconsistence in Russian Balkan policy in the 1990s. Nevertheless, Russia was able to preserve an integral vision of the region and even to elaborate new transregional constructive projects, which in right political circumstances may promote stability and become beneficial for both Russia and the Euro-Atlantic community.